Narrativa transmedia y educación ambiental infantil. Principios creativos y pautas metodológicas - Montalvo Castro, Jorge Andrés (2012)
How can we incorporate transmedia storytelling in a children's environmental education project that uses television and internet? In this paper we propose some criteria and principles as a result of a research sponsored by the Institute for Scientific Research-IDIC from the University of Lima. Based on a practical experience we formulate guidelines for selecting media and formats, developing stories and characters, and the design of materials. We also discuss the particularities of the creative process in transmedia educational projects.